Patient Perspectives on the Use of Categories of Conditions for Decision Making About Genomic Carrier Screening Results. Issue 7 (July 2018) - Kraft, Stephanie A.; McMullen, Carmit K.; Porter, Kathryn M.; Kauffman, Tia L.; Davis, James V.; Schneider, Jennifer L.; Goddard, Katrina A. B.; Wilfond, Benjamin S.
Abstract : (Abstracted from Am J Med Genet 2018;176A:376–385) Rapid, affordable genome sequencing in reproductive medicine continues to increase in availability and popularity, with some commercial laboratories now offering expanded carrier panels for all patients. This trend presents clinicians with new challenges in presentation and supporting patients' decisions as they decide whether to receive expanded, genome-scale carrier screening.